Legal issues in BYOP: Bring Your Own Persona - McNealy, Jasmine (AoIR Selected Papers of Internet Research, 2013)
Increasingly businesses are requiring or encouraging employees to maintain a presence on social media either through personal media use or control of a corporate account. This paper defines this kind of social media use as Bring Your Own Persona, as corporations are using the social media popularity of their employees for potential economic gain. But issues surrounding employee use and control of social media are emerging, causing businesses to go to court to assert social media account ownership, or to defend against claims of unauthorized access. This paper examines the court cases that have arisen connected to BYOP.